ANALISIS HADIS TEMPAT YANG DICINTAI DAN DIBENCI ALLAH DALAM KITAB SHAHIH IBNU HIBBAN - Mahfuz Munawar, Ali; Habibullah, Ilham; Azzahra, Khilya; Ramadhania Fitri, Mutiara (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2024)
The study of hadith requires methodological requirements for hadith which seem very complicated, because understanding hadith must go through two phases, namely the originality research phase of the hadith and the content analysis (matan) phase of the hadith. In this discussion, the hadith that will be analyzed is the hadith about the country that Allah loves is the mosque and the country that is hated is the market, which is quoted from the book Shahih Ibn Hibban written by Imam Ibnu Hibban. Among the scholars who are classified as transmitters of mutasahil, one of them is Ibn Hibban. In essence, a mosque is noble, not because it is noble in essence, but because of the virtuous human behavior in it, such as dhikr, reading Qur’an, prayers, and knowledge gatherings. In conclusion, the second hadith of places that Allah loves and hates is that Allah hates markets because of the evil done by humans in them, both in terms of commerce and communication between people. There is nothing wrong with activities in the market as long as we can protect ourselves from actions that can harm others or even things that can distract us from God. Through the analysis of the Takhrij Hadith we find that the degree of the hadith that has been discussed is authentic, there is no syadz or 'illah in the matan, the degree of the narrators of most of the tsiqqah strengthens this hadith so it can be concluded that this hadith is authentic and acceptable. This hadith is included in the marfu' hadith because it is attributed directly to Rasulullah SAW, and is a qauli hadith or words of the Prophet to a friend, namely Abu Hurairah. There is no shawahid in the transmission of this hadith because of Rasulullah SAW. Just convey it to Abu Hurairah.